Timing and Duration of Observation Periods of Foraging Behavior in Natural Grasslands - Jochims, Felipe; Soares, Émerson Mendes; de Oliveira, Leandro Bittencourt; Kuinchtner, Bruno Castro; Casanova, Pedro Trindade; Marin, Luciana; de Quadros, Fernando Luiz Ferreira (Frontiers in Veterinary Science, 2020)
The goals of this work were to evaluate for how long grazing should be monitored over a 24 hour period to predict grazing behavior of beef heifers within a season and check the patterns of foraging activity over 24 hours. Database was collected between 2010-2012 with beef heifers managed under rotational grazing in natural grassland. Grazing, rumination and other activities times were assessed visually during 24 hours in 15 occasions. Data were classified according to climatic seasons, generating 12 replicates in summer, 18 in spring, 24 in autumn and 36 replicates in winter. Treatments were the evaluation of four distinct periods of time: from sunrise to sunset (DAY-SUN), daylight duration from dawn to nightfall (DAYLIGHT), DAYLIGHT plus two hours (DAYLIGHT+2), DAYLIGHT to midnight (DAYLIGHTto0) and the entire 24 hours (CONTROL). Differences for grazing, rumination and other activities were found for all seasons among evaluation periods tested. Sampling sufficiency was reached only between the DAYLIGHTto0 and CONTROL for all four climatic seasons. The DAYLIGHTto0 treatment covered 75% of a 24 hours period and 95% of the mean foraging time taking place during this time interval. Considering grazing distribution over the day, in the warm seasons, the major grazing period during mornings occurred earlier than in the cool seasons and in cool seasons the grazing peak was observed during the afternoons. Visual observations starting at dawn until the mid-night hour were able to represent the total grazing time and natural behavior of heifers and it could be used to represent grazing activities during the entire day.